The Ontario Labour Relations Board and the Part Time Workers - Pupo, Norene; Duffy, Ann (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1988)
This paper examines Ontario Labour Relations Board decisions regarding the inclusion of part-time workers in bargaining units front 1976 to 1986.